Culture of neural stem cells in calcium alginate beads. - Li, X; Liu, T; Song, K; Yao, L; Ge, D; Bao, C; Ma, X; Cui, Z (2006)
Neural stem cells (NSCs) with the capacity of extensive self-renewal and multilineage differentiation have attracted more and more attention in research as NSCs will play an important role in the nerve disease treatment and nerve injury repair. The shortage of NSCs, both their sources and their numbers, however, is the biggest challenge for their clinic application, and hence, in vitro culture and expansion of NSCs is vitally important to realize their potentials. In this work, mouse-derived NSCs were cultured in three-dimensional calcium alginate beads (Ca-Alg-Bs). Gelling conditions, cell density, and cell harvest were determined by the exploration of formation and dissociation parameters for Ca-Alg-Bs. Additionally, the recovered and the subsequent induced cells were identified by immunofluorescence staining of Nestin, beta-tubulin, and GFAP. The results show that the 2-mm diameter Ca-Alg-Bs, prepared with 1.5% sodium alginate solution and 3.5% CaCl2 solution and with gelling for 10 min, is suitable for the NSCs culture. The seeding density of 0.8 x 10(5) cells x mL-1 for the encapsulation of NSCs resulted in the most expansion, and the NSCs almost doubled during the experiment. The average cell recovery rate is over 88.5%, with the Ca-Alg-Bs dissolving in 55 mM sodium citrate solution for 10 min. The recovered cells cultured in the Ca-Alg-Bs still expressed Nestin and had the capacity of multilineage differentiation into neurons and glial cells and, thus, remained to be NSCs. These results demonstrate that NSC expansion within Ca-Alg-Bs is feasible and provides further possibilities for NSC expansion in bioreactors of the scale of clinical relevance.